2020
DOI: 10.3389/fimmu.2020.01475
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Deep Sequencing Identifies a Unique miRNA Signature Released in Serum Exosomes in a Mouse Model of Sjögren's Syndrome

Abstract: Sjögren's Syndrome (SS) is an autoimmune disease characterized by lymphocytic infiltration and loss of function of moisture-producing exocrine glands as well as systemic inflammation. SS diagnosis is cumbersome, subjective and complicated by manifestation of symptoms that overlap with those of other rheumatic and ocular diseases. Definitive diagnosis averages 4–5 years and this delay may lead to irreversible tissue damage. Thus, there is an urgent need for diagnostic biomarkers for earlier detection of SS. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…Exosomal transfer of miRNAs from the bone marrow may promote breast cancer cell dormancy in a metastatic niche [ 63 ]. Moreover, a finding indicated that differential expression of miRNA-127-3p, miRNA-409-3p, miRNA-410-3p, miRNA-541-5p and miRNA-540-5p may result in the destruction of inflammation pathways in sicca syndrome mice [ 64 ]. Additionally, Exosomes miR-18b derived from cardiogenic cells improved ischemia–reperfusion injury in MI rats via inducing macrophage activation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal transfer of miRNAs from the bone marrow may promote breast cancer cell dormancy in a metastatic niche [ 63 ]. Moreover, a finding indicated that differential expression of miRNA-127-3p, miRNA-409-3p, miRNA-410-3p, miRNA-541-5p and miRNA-540-5p may result in the destruction of inflammation pathways in sicca syndrome mice [ 64 ]. Additionally, Exosomes miR-18b derived from cardiogenic cells improved ischemia–reperfusion injury in MI rats via inducing macrophage activation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…LC–MS analysis of saliva and tear EVs of pSS patients can screen new biomarkers that may contain saliva and lacrimal gland disease targets, which can improve the diagnostic accuracy of pSS and may also be used for disease staging and monitoring [ 45 , 46 ]. Recently, Kakan et al [ 47 ] used small RNA deep sequencing to identify the characteristics of serum exosome miRNA in early and middle autoimmune lacrimal gland inflammation and pSS mouse models. They found seven miRNAs with the most significant differences in expression.…”
Section: Research Progress On Extracellular Vesicles In the Pathogene...mentioning
confidence: 99%
“…In total, 13 samples were sent for RNA sequencing, and raw data was analyzed as follows: (A1) Quality assessment by FASTqc showed presence of 3' adapters in the reads; (B) Using cutadapt (33), 3' adapters were trimmed and reads with quality scores <20 or length <15 were removed; (C) Trimmed reads were aligned to mouse genome GRCm38 using Bowtie (34); and (D) Aligned reads were annotated using featureCounts (35). Additionally, (A2) raw FASTQ files were also run through our internal miRGrepp pipeline (36) and (E) miRNA counts were normalized, and plotted to assess the quality of the data with statistics on these read counts performed using R package, DESEq2 (37); (F) Shortlisted hits were validated by qPCR in a separate cohort of mice; and and (G) Pathway analysis of the hits was done in Ingenuity Pathway Analysis (Qiagen). Graphic created with BioRender.com.…”
Section: Animalsmentioning
confidence: 99%
“…Trimmed reads were aligned to mouse whole genome GENCODE GRCm38 using Bowtie and quantified using featureCounts. Raw reads were also aligned to miRbase v22.0 as described previously (36) using our in-house aligner miRGrep (36). miRNA read counts filtering, data normalization, and differential gene expression analysis was done using DESEq2 in RStudio with no data points excluded in the analysis.…”
Section: Library Preparation Ngs and Bioinformatics Analysismentioning
confidence: 99%